Kedudukan Tasrih Haji dan Korelasinya dengan Syarat Wajib dan Mabrur Haji - Yusra, Hannilfi (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2024)
This research discusses the situation where many pilgrims do not have tashrih in performing Hajj. Where the purpose of this study is to determine the correlation of tasrih to the mandatory requirements of Hajj and the position of the predicate status of the pilgrims. The research method used is qualitative, namely literature with an explanatory approach. The primary data source is Law No. 8 of 2019 concerning the Implementation of Hajj and Umrah (PIHU). Data was collected with documentation and conclusions were drawn with descriptive analysis techniques. The research findings state that tasrih is an official permit issued by the government of Saudi Arabia for pilgrims who want to visit Raudhah in the implementation of Hajj. If pilgrims do not have tasrih, they will be arrested and deported by the Saudi Arabian authorities because they do not have complete administrative requirements as a mandatory requirement for Hajj participants in carrying out their religious rituals. Regarding the title of mabrur Hajj, they are literally not included in the category because they performed Hajj fraudulently or illegally. However, those who are fortunate enough to perform Hajj without this authority (tasrih), their Hajj is still considered valid